Pre-trial investigation bodies in Ukraine and EU countries: a comparative legal analysis - Chaika, R. A. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article presents a study of the institutional mechanism of pre-trial investigation in Ukraine in comparison with analogous models operating within the legal systems of selected European Union countries – namely the Federal Republic of Germany, the Republic of Poland, and the French Republic. The analysis of the Ukrainian model emphasizes its complex structure, comprising five principal bodies – the National Police, the Security Service of Ukraine, the State Bureau of Investigation, the National Anti-Corruption Bureau, and the Bureau of Economic Security – each vested with statutorily defined jurisdiction. Particular attention is given to the institute of inquiry (дізнання), which since 2020 has functioned as a separate procedural form for investigating criminal misdemeanors. The article highlights that such institutional multiplicity entails risks of jurisdictional conflicts and duplication of authority, which adversely affects the efficiency and promptness of investigations. The comparative overview of the German model demonstrates its centralized nature: all investigative actions are carried out by the police under the procedural direction of the public prosecutor, who acts as the primary authority in determining whether public charges should be filed. The Polish system illustrates a combination of centralized prosecutorial oversight with the delegation of investigative powers to various specialized agencies, while preserving the unifying role of the prosecutor. The French model is characterized by a two-stage structure of pre-trial proceedings, combining police inquiry and judicial investigation, the latter conducted by an investigating judge – an independent procedural figure authorized not only to approve but also to initiate and carry out investigative measures in complex cases. Based on the comparative legal analysis, the article identifies several relevant directions for improving the Ukrainian model: the implementation of clear coordination mechanisms among investigative bodies; strengthening the role of the prosecutor as the sole procedural leader; simplifying proceedings for minor offenses; and potentially introducing elements of judicial investigation for certain categories of criminal cases. While the article stresses the inadvisability of direct transplantation of foreign models without consideration of domestic legal specificities, it underscores the value of gradually adapting the most effective European practices within the broader framework of criminal procedure harmonization.